2020
DOI: 10.3390/en13051051
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization of Enzymatic Hydrolysis of Apple Pomace as Feedstock for a Sugar-Based Biorefinery

Abstract: The enzymatic hydrolysis of cellulose from biomass feedstock in the sugar-based biorefinery chain is penalized by enzyme cost and difficulty to approach the theoretical maximum cellulose conversion degree. As a consequence, the process is currently investigated to identify the best operating conditions with reference to each biomass feedstock. The present work reports an investigation regarding the enzymatic hydrolysis of apple pomace (AP). AP is an agro-food waste largely available in Europe that might be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Other attempts to adjust the long-term prevision of sugar production dynamics and yields included the use of product inhibition [14,15] and biomass recalcitrance [16] as additional terms of the kinetic model. In addition, diffusion limited models, such as Chrastil's model [17] (see equation in Table 1), can be safely applied if the limit conversion (maximum sugar concentration) is provided by bench scale tests [18,19]. This type of model is aimed at describing the effect of substrate structure on the rate of glucose production, so, in addition to the kinetic parameter k, the n parameter describes the effect of soluble species diffusion into the porous structure of the biomass (n→1 negligible diffusion limitation, 0 < n < 1 diffusion limited regime).…”
Section: Kinetic Models Of Enzymatic Cellulose Hydrolysismentioning
confidence: 99%
See 3 more Smart Citations
“…Other attempts to adjust the long-term prevision of sugar production dynamics and yields included the use of product inhibition [14,15] and biomass recalcitrance [16] as additional terms of the kinetic model. In addition, diffusion limited models, such as Chrastil's model [17] (see equation in Table 1), can be safely applied if the limit conversion (maximum sugar concentration) is provided by bench scale tests [18,19]. This type of model is aimed at describing the effect of substrate structure on the rate of glucose production, so, in addition to the kinetic parameter k, the n parameter describes the effect of soluble species diffusion into the porous structure of the biomass (n→1 negligible diffusion limitation, 0 < n < 1 diffusion limited regime).…”
Section: Kinetic Models Of Enzymatic Cellulose Hydrolysismentioning
confidence: 99%
“…As an example, the selection of proper mixing conditions is hardly considered among the operational parameters that influence the validity of bench-scale hydrolysis tests, and Gan et al [21] observed how most of the studies ignore the effects of external mass transfer on the overall sugar production rate. Pratto et al [18] and Procentese et al [19] proved that the mixing rate should be selected first since the initial glucose production rate (over 60 min) is highly affected by the mixing speed. They assessed the threshold value of mixing speed, above which a constant glucose production rate was observed.…”
Section: Kinetic Models Of Enzymatic Cellulose Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic hydrolysis is the process of using enzymes to break down cellulose into soluble glucose, which can then be used to produce paper, cotton textiles, and biofuels such as ethanol [16]. Enzymatic hydrolysis strongly depends on the operating conditions of the process (such as temperature, solids loading, enzyme loading, and pH), enzyme consumption (specific activity, enzyme recycling strategies, and stability), and the effect of product inhibitor on enzyme catalysis [17]. Normal enzymatic hydrolysis applied directly to raw lignocellulosic biomass is not effective in extracting the cellulose as the lignin remains intact and unaffected by the process [18].…”
Section: Introductionmentioning
confidence: 99%